2022
DOI: 10.1002/clt2.12123
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of monotherapy with biologicals for children and adults with IgE‐mediated food allergy

Abstract: Background Biological therapies relieve symptoms in allergic inflammatory diseases so we systematically reviewed the evidence about whether biological monotherapy could benefit people with IgE‐mediated food allergy. Methods We searched six bibliographic databases from 1946 to 30 September 2021 for randomised and non‐randomised controlled trials about biological monotherapy in people with IgE‐mediated food allergy confirmed by oral food challenge. We used the Grading of Recommendations, Assessment, Development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…At the same time, the degree to which epitopes cover a significant portion of the surface of trimers and individual monomers is consistent with challenges associated with addressing allergenicity of these proteins in food ( de Silva et al, 2022 ). To gain more insight into epitope coverage across 7S globulins, the Ara h 1 epitopes identified by Cabanos et al and the Gly m 5.01 epitopes listed by Pi et al, were mapped onto the trimeric crystal structure of Ara h 1 ( Fig.…”
Section: Discussionsupporting
confidence: 60%
“…At the same time, the degree to which epitopes cover a significant portion of the surface of trimers and individual monomers is consistent with challenges associated with addressing allergenicity of these proteins in food ( de Silva et al, 2022 ). To gain more insight into epitope coverage across 7S globulins, the Ara h 1 epitopes identified by Cabanos et al and the Gly m 5.01 epitopes listed by Pi et al, were mapped onto the trimeric crystal structure of Ara h 1 ( Fig.…”
Section: Discussionsupporting
confidence: 60%
“…The study generated promising evidence for the intravenous administration of Etokimab in the treatment of peanut allergy [35]. A systematic review from 2021 compared this study with other biologicals [36 ▪▪ ].…”
Section: Alarmin-targeted Treatmentsmentioning
confidence: 99%
“…Etokimab, an antagonist of IL-33, has been recently studied for IgE-mediated peanut allergy, while no clinical trials with tezepelumab in food allergy have been reported. Large, randomised trials are needed to assess the safety, efficacy, posology and the most suitable candidates for such treatments [ 92 , 93 ]. The rationale for such studies derived initially from the functional role of TLSP in food allergy revealed in murine model studies [ 94 ].…”
Section: Tslp In Urticaria Atopic Dermatitis and Food Allergymentioning
confidence: 99%